Penerapanan Internet 0f Things (IoT) Dalam Membangun Sistem Aplikasi Kendali Rumah Kos Menggunakan Aplikasi Android - UC Mariance; Irwan; Muhammad Aqsal Raihan Lubis (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Internet of Things (IoT) devices are now starting to be widely used, one of which is IoT Monitoring. The use of electricity by boarding house tenants is often negligent, they feel they have paid the boarding fee and are wasting electricity even though it is not used, for example, the lights in a boarding room where there are no people inside. Likewise with the bathroom if the water tub is full, often the occupants of the boarding house are indifferent to water. The use of ACS712 and ZMPT101B sensors to see the electricity usage of each boarding room. Boarding room security is strengthened by the use of RFID modules and PPIR sensors. Electrical tools and Solenoid Door Lock can be controlled via an android application. The accuracy of the sensor reading electricity usage is still below normal limits, namely 0.11% -0.74% for volts, and 0.72% -3.84% for current. In sending orders from the android application there is a delay in the response of the device due to factors that cannot be calculated, namely internet connection